COMMUNITY-BASED FOOD SECURITY EFFORTS IN THE FRAMEWORK OF NUTRITION FOLLOWING MOTHER AND CHILDREN IN THE PANDEMIC Period (COVID - 19): LITERATURE REVIEW - Siti Maryani; Noviyati Rahardjo Putri (Journal of Midwifery Science: Basic and Applied Research, 2020)
Background The effects of the COVID-19 pandemic covers all aspects of life, one of which is food security (Masniadi, Angkasa, Karmeli, Esabella, 2019). The number of malnutrition especially among mothers and children globally during the pandemic is increasing. Pandemics can increase poverty, cut food supply chains and malfunction in nutrition education programs for the community (Akseer, Kandru, Keats, Bhutta, 2020). The effects of the pandemic also have an impact on the nutritional adequacy of mothers and children (including infants and toddlers) in Indonesia. The availability of household food, limited access and affordability of healthy food ingredients are the three main problems in the scope of fulfilling nutrition during the pandemic in Indonesia (Unicef Indonesia, 2020). The method in this research is literature review, the journals used in the literature review are obtained through a database of international journal providers such as Google Scholar, Pubmed, and Proquest. Researchers write the appropriate keywords, namely food security and pandemic. The year limit used is 10 years, namely 2010 to 2020. Results and discussion of online surveys show that 36% of respondents “often reduce” their food portions due to financial problems, of course this will affect the nutritional status of the family, especially children and mothers (Unicef Indonesia, 2020). However, regional research in one district shows that the nutritional status of children aged 3 - 5 years is not affected by this pandemic. Although data on the mapping of the impact of a pandemic on nutritional status is still limited, it is hoped that the community will be able to maintain family nutrition adequacy with various household-based efforts that can be implemented effectively and efficiently. Keywords: Food Security, Nutrition, Pandemic Period